Reflective Mediation: Toward a Sociocultural Conception of Situated Reflection - Dalsgaard, Christian (Frontline Learning Research, 2020)
The objective of the article is to contribute to the development of a sociocultural conception of situated reflection that can be used in empirical studies of reflection, and that can be utilised in development of educational practices. Based on a development of the concept of ’reflective mediation’, a conception of reflection is developed from a situated understanding of learning processes. Taking a situated approach, the concept of reflective mediation describes how to understand reflection as an integral part of the immediate activities of the individual. A theoretical framework is developed for empirical studies on reflective activities of higher education students. The framework can be utilised by teachers to develop teaching methods in support of reflection in student learning. The concept of reflective mediation is developed from a combination of pragmatism and cultural historical activity theory, and it covers seven categories of learning and reflection processes. The article makes a distinction between three forms of mediation, two forms of empirical reflection, and two forms of theoretical reflection. The article concludes in a discussion of the implications of the theoretical framework for educational research and for teaching practices within higher education. The article is frontline in the sense that it aims at developing a theoretical conception of situated reflection by combining cultural historical activity theory with pragmatism and theories of situated learning. The novelty of the article is to consider levels of human activity as levels of reflection and to introduce the distinction between theoretical and empirical reflection. Further, the article provides arguments that awareness of objects and instruments of human activity forms the basis of reflective processes. Finally, the article explains how reflection can connect levels of human activity and learning.